Evaluation of social cognitive measures in an Asian schizophrenia sample - Lim, Keane (2020)
Background: Converging evidence has indicated that deficits in social cognition may manifest as poor functioning; therefore, social cognition has emerged as an important research area and treatment target. However, few studies have examined the psychometrics of multiple social cognition measures in an Asian population. This study aims to evaluate the psychometrics of measures indexing the four core social cognition domains. Methods: Schizophrenia outpatients (n = 116) and healthy controls (n = 73) completed a battery of nine social cognitive measures, twice, four weeks apart. Psychometric properties were examined via test-retest reliability, internal consistency, utility as a repeated measure, time administration, and tolerability. Logistic regression was performed to identify psychometrically sound tasks that best discriminated case-control status. PCA was conducted to explore social cognition dimensional structure. Results: The Bell Lysaker Emotion Recognition Task (BLERT), Penn Emotion Recognition Task (ER40), and The Awareness of Social Inference Test, branch III (TASIT-3) showed strongest psychometrics. The Ambiguous Intentions and Hostility Questionnaire, Hostility Bias subscale (AIHQ-HB) showed slightly weaker properties, requiring further evaluation. The Hinting task, Mini Profile of Nonverbal Sensitivity (MiniPONS), Relationships Across Domains (RAD), Internal Personal and Situational Attributions Questionnaire (IPSAQ), and Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) showed poorer psychometrics in our sample. PCA revealed a two-factor solution comprising social cognition skills and attributional style/bias. Conclusion: Here, we examined the psychometric properties of a comprehensive social cognition battery based on the SCOPE study in an Asian schizophrenia population. Continued evaluation and standardization of social cognitive measures are needed to refine our understanding of this construct in schizophrenia.